The Dance Lessons in Batik SMPLB B Manunggal District Tegal Slawi - Wardani, Anestia Widya; Triyanto, Triyanto; Hartono, Hartono (Universitas Negeri Semarang, 2019)
School (SLB) Manunggal Slawi is one special school run by the foundation